Unveiling the gut-liver axis: the behind-the-scenes “manipulator” of human immune function - Li, Peizhe; Wang, Yu; Dong, Yanan; Zhang, Xin (Frontiers in Immunology, 2025)
The “gut-liver axis” enables bidirectional immunoregulation between the intestine and the liver through the portal venous circulation, bile acid metabolism, and the neuro-lymphatic network. This paper reviews its physiological pathways (vascular, biliary, neural, and lymphatic), immunomodulatory mechanisms (interaction of innate/adaptive immune cells, balance between inflammation and tolerance), and associations with diseases such as PSC, MAFLD, and IBD. Metabolites of gut microbiota activate immune cell receptors to regulate the differentiation of Tregs, while cytokines (such as IL-6) and chemokines (such as CCR9) drive the synergy of gut-liver immunity. In pathological conditions, dysbiosis, endotoxin translocation, and bile acid metabolic disorders trigger immunological dysregulation through this axis. Strategies such as targeted fecal microbiota transplantation and bile acid receptor (FXR) agonists show clinical potential. This paper systematically elaborates on the physiological and immunoregulatory mechanisms of the “gut-liver axis”, explores the associations between its abnormalities and immune diseases, as well as the prospects of translational medicine. It is proposed that future research should deepen the analysis of single-cell interactions, conduct personalized interventions, and establish a new paradigm of “gut-liver axis medicine” to provide cross-organ solutions for the precise prevention and control of immune-related diseases.